Determination of ammonia based on the electro-oxidation of hydroquinone in dimethylformamide or in the room temperature ionic liquid, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide. - Giovanelli, D; Buzzeo, M; Lawrence, N; Hardacre, C; Seddon, K; Compton, R (2004)
The results detail a novel methodology for the electrochemical determination of ammonia based on its interaction with hydroquinone in DMF. It has been shown that ammonia reversibly removes protons from the hydroquinone molecules, thus facilitating the oxidative process with the emergence of a new wave at less positive potentials. The analytical utility of the proposed methodology has been examined with a linear range from 10 to 95ppm and corresponding limit-of-detection of 4.2ppm achievable. Finally, the response of hydroquinone in the presence of ammonia has been examined in the room temperature ionic liquid 1-ethyl-3-methylimidazolium bis(trifluormethylsulfonyl)imide, [EMIM][N(Tf)(2)]. Analogous voltammetric waveshapes to that observed in DMF were obtained, thereby confirming the viability of the method in either DMF or [EMIM][N(Tf)(2)] as solvent.